Development of a zeolite washcoating technique for microchannel reactors - Truter, Lara (Department of Chemical Engineering, 2015)
Microreactor technology is becoming an increasingly active research field in terms of chemical reaction engineering and process intensification. An important feature of microreactor technology is the requirement of a catalyst layer.